Impact of particulate matter on basmati rice varieties grown in Indo-Gangetic Plains of India: Growth, biochemical, physiological and yield attributes. (September 2018) - Mina, U.; Chandrashekara, T.K.; Kumar, S. Naresh; Meena, M.C.; Yadav, S.; Tiwari, S.; Singh, Deepak; Kumar, Pranav; Kumar, Ram
Abstract: The study presents the first experimental evidence of the effects of atmospheric particulate matter (PM) deposition on two basmati (scented) rice varieties [Pusa Basmati-1509 (PB-1509) and Pusa Sugandh-5 (PS-5)] grown in Indo-Gangetic Plains (IGP) of India. Atmospheric PM load at the experimental site during rice crop growth period (August–November) was in the range of 162–660 μgm −3 . The rice varieties growth, biochemical, physiological and yield attributes were monitored under three levels of PM deposition namely - low levels of PM deposition (LPM), ambient levels of PM deposition (APM) and elevated levels of PM deposition (EPM). PM deposition and PM flux on the canopy of rice varieties were 400–574 μgcm −2 and 24–58 μgcm −2 day −1, respectively. PM deposition was 4.5% higher on the PS-5 than PB-1509 and among growth stages; it was the highest during the reproductive growth stage. Significant reduction in chlorophyll, leaf water and carotenoid content were observed in both varieties under EPM compared to APM. The air pollution tolerance index (APTI) also declined significantly. PM deposition enhanced leaf temperature (1–6%) of rice varieties under EPM compared to APM. The reduction in photosynthesis, stomatal conductance and transpiration of rice varieties under EPM were in the range of 9–52%; 6–40% and 8–46%, respectively compared to APM. PM deposition effects on plant height, the number of tillers and recoverable root biomass were found non-significant. PS-5 and PB-1509 exhibited 4–7% enhancement and 7.5–14% reduction in grain yield under LPM and EPM compared to APM, respectively. The results of the study indicate that increasing atmospheric PM pollution in IGP may adversely affect productivity and economic gains from scented basmati varieties of rice. Graphical abstract: Impact of atmospheric pm on rice varieties. Image 1 Highlights: Cumulative PM deposition (1183–3551 μgcm −2 ) adversely affected rice productivity. Cumulative PM deposition was 19–35% higher on the canopy of PS-5 than PB-1509 variety. PM deposition clogged the stomatal opening and enhanced the leaf temperature (1–6%) in rice cultivars. Gaseous exchange is adversely affected in rice plants due to PM deposition. PM induced yield reduction is high in rice genotype PS-5 (14.9%) than PB-1509 (11.9%).